MACROSEISMICITY AND GEOLOGICAL EFFECTS OF THE WENCHUAN EARTHQUAKE (MS 8.0R - 12 MAY 2008), SICHUAN, CHINA: MACRO-DISTRIBUTION AND COMPARISON OF EMS1998 AND ESI2007 INTENSITIES - Lekkas, E. (Bulletin of the Geological Society of Greece, 2010)
The Wenchuan earthquake of the 12th of May 2008, in Sichuan county of China can be classified as a large scale event based on the tectonic structures that triggered the earthquake and the effects caused on the human, structural and natural environment. The aim of this paper is to present the geotectonic and seismotectonic regime of the earthquake affected region based on field data along the seismic fault zone and an attempt is made towards the: (i) estimation of the intensity values according to EMS1998 (European Microseismic Scale, 1998) and ESI2007 (Environmental Seismic Intensity Scale, 2007) and the determination of their geographical distribution in a macroscale, (ii) interpretation of the intensity values data and their distribution according to the seismotectonic, geodynamic and geotechnical regime, and (iii) conduction of a comparative evaluation review on the application of both EMS1998 and ESI2007. The application of both EMS1998 and ESI2007 and the comparative evaluation of the results indicate that the estimated values of EMS1998 and ESI2007 were almost in agreement, despite the fact that the geographical locations of assessment data were different suggesting that the application and use of both scales appears to represent a useful and reliable tool for seismic hazard estimation.